Anatomical Step-by-Step Dissection of Complex Skull Base Approaches for Trainees: Surgical Anatomy of the Posterior Petrosal Approach - Graffeo, Christopher S.; Peris-Celda, Maria; Perry, Avital; Carlstrom, Lucas P.; Driscoll, Colin L.W.; Link, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction Although numerous anatomical and operative atlases have been published, those that have focused on the skull base either have provided views that are quite difficult to achieve in the operating room to better depict surgical anatomy or are written at the level of an audience with considerable knowledge and experience.Methods Five sides of three formalin-fixed latex-injected specimens were dissected under microscopic magnification. A posterior petrosectomy approach was performed by three neurosurgical residents at different training levels with limited previous experience in anatomical dissection mentored by the senior authors (C. L. W. D. and M. J. L.) and a clinical skull base fellow with additional anatomical dissection experience (M. P. C.). Anatomical dissections were performed until the expected level of dissection quality was achieved to demonstrate each important step of the surgical approach that would be understandable to all trainees of all levels. Following dissection education, representative case applications were reviewed.Results The posterior petrosectomy (also known as presigmoid retrolabyrinthine approach) affords excellent access to cranial nerves III to XI and a diverse array of pathologies. Key steps include positioning and skin incision, scalp and muscle flaps, burr holes, craniotomy flap elevation, superficial mastoidectomy, otic capsule exposure and presigmoid dura decompression, primary presigmoid durotomy, inferior temporal durotomy, superior petrosal sinus ligation, tentorium sectioning, and final exposure.Conclusion The posterior petrosectomy is a challenging approach; thorough operative-style laboratory dissection is essential to provide trainees with a suitable guide. We describe a comprehensive approach to learning this technique, intended to be understandable and usable by a resident audience.
Keywords: posterior petrosectomy; meningioma; brainstem; skull base; education